[Addendum to Protocol 5007: interrogation of Harald Utne.] (1943)
Addendum to the interrogation of Norwegian Harald Utne dated September 9, 1943. Taken from microfilm Records of the German Field Command, Armies, National Archives Series T-315, Reel 1621, 210 Inf. Div. Ic, Annex 2, KTB 3, Folder 45787/3, first frame 000507. Translated by Major James F. Gebhardt, USA (retired)